1978
DOI: 10.1002/jbm.820120103
|View full text |Cite
|
Sign up to set email alerts
|

Histologic response to porous PMMA implant materials

Abstract: Poly(methyl methacrylate) as used in polymer replica tooth implants was fabricated into 6 X 6 mm cylindrical specimens and cured in either an air oven, pressure pot, autoclave, or microwave oven. Polymer porosity was achieved by means of either 1) intrinsic foaming agents, or 2) compacting different sizes of large beads with a minimum of monomer, with dense PMMA used as a control. Specimens were then implanted in the long bones of baboons. Histology of thin-sectioned and ground specimens from the sacrificed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1984
1984
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 18 publications
(2 reference statements)
0
9
0
Order By: Relevance
“…First, although porous PMMA has been well studied, 24,27,[36][37][38][39] including porous PMMA fabricated using an aqueous phase consisting of a CMC hydrogel as a porogen, 25,40 the present study is one of the first systematic studies of fabrication methods to quantitatively examine the effect of both the ratio of aqueous phase to polymer phase but also the effect of the aqueous phase viscosity as done by varying the amount of CMC within the aqueous phase. Increasing the viscosity of the aqueous phase by using a 9 wt% CMC hydrogel, as opposed to a 7 wt% CMC gel as has been previously used, 41 resulted in a more consistent pore architecture with smaller, more consistently sized pore interconnections.…”
Section: Discussionmentioning
confidence: 99%
“…First, although porous PMMA has been well studied, 24,27,[36][37][38][39] including porous PMMA fabricated using an aqueous phase consisting of a CMC hydrogel as a porogen, 25,40 the present study is one of the first systematic studies of fabrication methods to quantitatively examine the effect of both the ratio of aqueous phase to polymer phase but also the effect of the aqueous phase viscosity as done by varying the amount of CMC within the aqueous phase. Increasing the viscosity of the aqueous phase by using a 9 wt% CMC hydrogel, as opposed to a 7 wt% CMC gel as has been previously used, 41 resulted in a more consistent pore architecture with smaller, more consistently sized pore interconnections.…”
Section: Discussionmentioning
confidence: 99%
“…Materials currently available in the clinic, such as polymethylmethacrylate (PMMA), generally do not meet the needs of the space maintenance application, and commonly result in infection and wound dehiscence 9, 11–13. However, porous PMMA has been previously shown to enhance integration with the surrounding soft and hard tissue, resulting in less dehiscence than solid PMMA 13–16. Notwithstanding, PMMA has been used for arthroplasty fixation and cranioplasty for decades with many advantages such as moldability and rapid setting time 17, 18.…”
Section: Introductionmentioning
confidence: 99%
“…15,22 Similar to this study, where the solid and porous groups performed similarly histologically, a 14 week study by Nathanson et al and a 12 week study by Kretlow et al showed no difference in histological assessment of solid or porous implants at the end time point. 13,23 Contrary to these studies, van Mullem et al observed porous implants with 50 wt% of CMC gel as the porogen were surrounded by well-vascularized fibrous tissue, while solid implants had a thick fibrous capsule in a long term study of 8 and 24 months, indicating the possibility for further remodeling of the surrounding tissue in the porous implant group, which could differentiate the histological scores. 24 …”
Section: Discussionmentioning
confidence: 95%